Knowledge of elderly cadres on dementia in Yogyakarta, Indonesia - Mulyani, Sri; Cahyani, Kadek Dewi; Listyaningrum, Desy; Ulayya, Aisyah Iffah (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: Dementia can cause disability, in addition to physical, mental, and financial stress for caregivers, and affect the nation’s healthcare system and economy. Efforts are needed to improve the quality of life of people with dementia involving various sectors, especially elderly cadres. Elderly cadres are volunteers who provide screening and health education for elderly persons at the community level. Accordingly, it is crucial to identify the knowledge levels about dementia in elderly cadres to improve public awareness and interventions concerning this topic. This study aimed to determine the level of knowledge of elderly cadres about dementia. Methods: This quantitative study was conducted with a cross-sectional design. There were 103 elderly cadres recruited using convenience sampling from November to December 2022. A demographic questionnaire and Dementia Knowledge Assessment Scale (DKAS) were used to collect the data. The data were analyzed using Spearman’s rho and Mann Whitney with significance set as p < 0.05. Results: The median score of the elderly cadres’ knowledge score was 22 (minimum-maximum = 0-44). Elderly cadres’ knowledge was related significantly to training about dementia (p = .002). There was no significant correlation between elderly cadres' knowledge and age (p = .271), gender (p = .073), and education level (p = .106). Conclusions: In general, the knowledge of elderly cadres about dementia is relatively low. However, there was a significant change in knowledge scores after dementia training, so a program to increase understanding about dementia through training is recommended for elderly cadres.